2020
DOI: 10.3390/s20143949
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Based Methodology for Fault Diagnosis in Electromechanical Systems

Abstract: Fault diagnosis in manufacturing systems represents one of the most critical challenges dealing with condition-based monitoring in the recent era of smart manufacturing. In the current Industry 4.0 framework, maintenance strategies based on traditional data-driven fault diagnosis schemes require enhanced capabilities to be applied over modern production systems. In fact, the integration of multiple mechanical components, the consideration of multiple operating conditions, and the appearance of combined fault p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The DAE architecture proposed by [ 47 ], trained layer by layer is adopted in this pa-per. The DAE hyperparameters, such as, the coefficient for the L2 regularization term, the coefficient for the sparsity regularization term and, the parameter for sparsity proportion, as well as the number of neurons in each hidden layer, are established from the search for the optimal configuration using a genetic algorithm (GA).…”
Section: Methodsmentioning
confidence: 99%
“…The DAE architecture proposed by [ 47 ], trained layer by layer is adopted in this pa-per. The DAE hyperparameters, such as, the coefficient for the L2 regularization term, the coefficient for the sparsity regularization term and, the parameter for sparsity proportion, as well as the number of neurons in each hidden layer, are established from the search for the optimal configuration using a genetic algorithm (GA).…”
Section: Methodsmentioning
confidence: 99%
“…So, the input of the anomaly detection model is the information contained in the features, and the output is an anomaly score that determines how different is the new measurement analyzed compared to those that has been trained (the reference). Full details of how to build the SAE model can be found in [15]. Since the DAE tends to perform a poor reconstruction with data different from those used for its training, the reconstruction error of the input data is expected to be a score of anomaly detection.…”
Section: Methodsmentioning
confidence: 99%
“…Result showed that the GDCCN provides better performance than conventional DL methods even in noisy enviroments and different workloads. Espitia et al 2020 64 & Espitia and Soto. 2020 65 used SAE based deep learning methodology for effective fault diagnosis in electromechanical systems.…”
Section: Based Motor Fault Diagnosismentioning
confidence: 98%